N-gram Language Models for Large-Vocabulary Speech Recognition - Silva, Ênio; Pantoja, Marcus; Celidônio, Jackline; Klautau, Aldebaro (Proceedings of the Brazilian Symposium in Information and Human Language Technology (STIL); 2004: Proceedings of the 2nd Workshop in Information and Human Language Technology, 2004)
This work describes preliminary results on N-gram language models applied to Brazilian Portuguese. The project is part of an effort to develop a large vocabulary continuous speech recognition system, where language modeling plays a fundamental role. We present a brief summary of state-of-art techniques, including the recently proposed interpolated additive (AI) model. We also describe simulation results, which show that the AI model is competitive with some well-established techniques.